A importância da gestão de indicadores de eficiência visando a melhoria contínua no processo de equipamentos físicos e moveis para manuseio e armazenagem de granéis - Cortiço, Felipe Oliveira (2023)
With increasing competitiveness in the industrial sector, it is increasingly necessary for companies to make their processes more efficient. It is common during the manufacturing process of physical and furniture equipment for bulk handling and storage, to detect production losses, reducing the efficiency of the production process. The present work presents an analysis of efficiency indicators, aiming to seek improvements in the equipment production process. With this, the analysis of efficiency indicators (OEE) made in a cutting equipment was presented and with the data obtained, opportunities for improvement were identified. After identifying opportunities for improvement, a plan was established to execute and monitor the changes implemented to improve the efficiency of the equipment. The results presented were satisfactory, achieving a 62% reduction in the time to change the equipment setup, which is equivalent to a gain of 30 hours in the equipment production process.